Production of a Glass Fiber Reinforced Polymer Matrix Composite by Injection Moulding and its Characterization - Karaaslan, Ahmet; Sabanci, Sender; Atapek, Hakan (WALTER DE GRUYTER GMBH, 2009)
Polymer matrix composites have a great importance and a wide range of fields of application due to their superior mechanical, physical, and chemical properties. Polymer matrix composites are generally used in aerospace, aircraft, chemical, defence, automotive, and medical industries. Matrix and fiber technologies have had a great development in the last 30 years. The major disadvantage of composite materials are the high production costs. Injection moulding techniques are very useful for production of short fiber reinforced polymer matrix composites. In this study, production of short fiber reinforced polymer matrix composites has seen examined and miscallenous reinforced and matrix materials are described.
Keywords: Materials Science